EVALUATION OF ANTIOXIDANT POTENTIALS OF LEAF AQUEOUS AND METHANOLIC EXTRACTS OF CALOPHYLLUM INOPHYLLUM IN RELATION TO TOTAL PHENOL AND FLAVONOID CONTENTS - SUMANA DUTTA,; SANJIB RAY, (International Journal of Pharma and Bio Sciences, 2014)
The leaves, barks, flowers, fruits and seeds of Calophyllum inophyllum are widely used in traditional practices. Here in the present study, we aimed to evaluate in vitro antioxidant potential of leaf aqueous and methanolic extracts of C. inophyllum in relation to total phenol and flavonoid contents. DPPH (1,1-diphenyl-2-picrylhydrazyl) free radical scavenging and ferric (Fe+3) reducing power was analyzed for antioxidant activity. The total phenol content was estimated using Folin-Ciocalteu reagent and flavonoid content was estimated spectrophotometrically (AlCl3) and calculated as tannic acid and quercetin equivalent respectively. DPPH free radical scavenging and Ferric (Fe+3) reducing the power of the leaf aqueous and methanolic extracts were increased with the increasing extract concentrations. Leaf methanolic extract of C. inophyllum (LMECI) showed more free radical scavenging activity and reducing power than the leaf aqueous extract of C. inophyllum (LAECI). Total phenol contents of aqueous and methanolic extracts were 97± 9.2 and 140.28± 17.1 mg/g respectively. Flavonoid contents of the aqueous and methanolic extracts were 88.94±2.94 and 177.06±5.29 mg/g respectively. The present study exhibited that the leaf methanolic extract of C. inophyllum have more free radical scavenging and reducing power than that of the aqueous extract. It may be due to the presence of relatively more total phenol and flavonoid contents in the leaf methanolic extract.